Traduire des jeux vidéo thérapeutiques pour enfants : entre localisation et vulgarisation médicale/Translating therapeutic video games for children: between localisation and medical vulgarisation - Jeanmaire, Guillaume; Kim, Jeong-yeon (The Journal of Specialised Translation, 2022)
As part of an international medical project, therapeutic video games were co-translated into thirteen languages for children with asthma in collaboration with pneumopediatricians, pharmacists, medical interns, translators, and IT specialists. Translation of these games differs from that of commercial games: longer deadlines, direct translation without the English pivot, possibility of viewing the game (translation in context) and editing the source text. The present study discusses the translation strategies related to health issues for young recipients. The findings show that regular exchanges among collaborators helped the translators to choose between translation, localisation, globalisation ("reversed localisation"), or even "re-creation" appropriately. In addition to medical knowledge, the translators must acquire the registers specific to the players' world and the language codes of the target audience. They must utilise creativity and humor to maintain emotions for game players while integrating technical data specific to each country.